Image segmentation encryption algorithm with chaotic sequence generation participated by cipher and multi-feedback loops - Deng, Jie; Zhou, Minjun; Wang, Chunhua; Wang, Sicheng; Xu, Cong (Multimedia tools and applications, 2021)
The existing chaotic image encryption algorithms have common defects: (i) ciphertext does not participate in the generation processes of chaotic pseudo-random sequences and key sequences; (ii) the entire encryption process does not have a closed-loop structure. In order to solve above problems, in this paper, an image segmentation encryption algorithm based on hyperchaotic system is proposed. We decompose the scrambled sequence into three sequences of different lengths: S 1 , S 2 and S 3 . Then, the initial values of the chaotic system are updated by the sequences S 2 and S 3 and using the updated initial value iterates the chaotic system and generates the key sequence K 3 , and the sequence S 1 is encrypted by the sequence K 3 to obtain the cipher sequence C 1 , using the sequences C 1 and S 3 updates the initial value of the chaotic system, and using the updated initial value iterates the chaotic system and generates the key sequence K 4 , and using the sequence K 4 encrypts the sequence S 2 to obtain the cipher sequence C 2 . Thus, ciphertext participates in the generation processes of chaotic pseudo-random sequences and key sequences, and the entire encryption process has a closed-loop structure. The experimental results show that the encryption algorithm has high security and sensitivity.